THE RELATIONSHIP BETWEEN ENVIRONMENTAL SANITATION WITH THE EVENT OF DIARRHEA IN TODDLERS - Umiati Umiati (Jurnal EduHealth, 2021)
The purpose of this study was to determine the relationship between the environment and the incidence of diarrhea in children under five in the working area of ​​the Nogosari Public Health Center, Boyolali Regency. This research method uses an observational design with a cross sectional approach. The subjects of this study were housewives who had toddlers and had suffered from diarrhea with a population of 328 people. The results showed that there was a relationship between drinking water sources (p = 0.001), latrine ownership (p = 0.018), type of house floor (p = 0.001). 0.036) with the incidence of diarrhea in children under five and there is no relationship between the physical quality of clean water (p = 0.307) with the incidence of diarrhea in children under five